THE CONCEPT OF PASSING THE STATE CIVIL SERVICE AND ITS DEVELOPMENT PROSPECTS - RAKHMONOV Zafarjon (Western European Studies, 2024)
This scientific article discusses the concept of public civil service, specific aspects of public civil service, its importance and relevance. Also, proposals were made regarding the introduction of the principle of meritocracy and the "career model" in public civil service in the Republic of Uzbekistan.
Keywords: public civil service; system of public civil service; principle of meritocracy